STRATEGY FOR THE DEVELOPMENT OF SMALL AND MEDIUM BUSINESSES IN THE CONTEXT OF DIGITAL TRANSFORMATION: RISKS, MARKETING TECHNOLOGIES AND MANAGEMENT CHALLENGES - ZHELIUK, Tetiana; BRECHKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
An important component of the formation of potential for post-war recovery and competitive development of Ukraine is small and medium-sized businesses. Security challenges, digital transformation act as a catalyst for systemic changes in the functioning of small and medium-sized businesses, determining fundamentally new management mechanisms at the regional level. The implementation of digital technologies allows small and medium-sized businesses to competitively position themselves in the market, modernize business processes and enhance the multiplier effects of entrepreneurial activity on the economy. The theoretical and methodological basis of the article is the fundamental provisions of modern economic science, the work of domestic and foreign scientists and practitioners. Within the framework of this study, several scientific approaches can be distinguished: institutional, systemic, marketing, innovative, process, synergistic, interdisciplinary. The research used methods of systemic, structural, factor, comparative analysis. Restraining and stimulating factors for the development of small and medium-sized businesses in the national economy have been identified. Vectors for the development of small and medium-sized businesses have been proposed within the framework of strategic planning for the development of territorial communities in the context of modern security challenges and the impact of digital transformations using marketing technologies and risk-based management. It has been proven that digital transformations are an imperative for the development of small and medium-sized businesses, determining qualitative changes in the system of management, communications and business strategy. The prospects for research into the development of small and medium-sized businesses should lie in the area of developing proposals to strengthen the role of local government in supporting innovative forms of business, using the potential of business for the post-war reconstruction of Ukraine and its territories.